Koefisien Pertumbuhan dan Panjang Infinity Geliona Erosa di Kawasan Ekosistem Mangrove Pesisir Barat Kabupaten Aceh Besar - M. Ali S (Universitas Syiah Kuala, 2010)
Mangrove oyster G. erosa undergo a process of growth and development. The process of growth occuring in this oyster of which is the length, width and weight. The process occurs since the ongoing growth process of conception until adulthood. The aim study is to determine (1) growth coefficient G. erosa, and (2) the length of infinity that can be achieved by the mangrove clam G. erosa in the area of the West Coast of Aceh Besar district. The study was divided into three locations, and observation was conducted in June-August 2009. In each set of four plots in each sample sampling size 10m x 10m and in each plot established 10 subplots each measuring 50cm x 50cm. All samples sampling subplots were damaged and done filtering to obtain G. erosa. The main result was the growth coefficient of mangrove oysters G. erosa in the western coastal area of Aceh Besar district was 0,230 mm, and length of infinity that can be achieved was 84.58 mm. Mangrove oyster G. erosa living in the mangrove ecosystem of the West Coast region of West Aceh Besar district, may reach a length of up to 84.58 mm.